Evolution of Magmatism in the New Hebrides Island Arc and in Initial Back-Arc Rifting, SW Pacific - Haase, Karsten; Gress, M. U.; Lima, Selma; Regelous, Marcel; Beier, Christoph; Romer, R. L.; Bellon, H. (Geochemistry Geophysics Geosystems, 2020)
We present new geochemical and isotopic data for rock samples from two island arc volcanoes, Erromango and Vulcan Seamount, and from a 500 m thick stratigraphic profile of lava flows exposed on the SW flank of Vate Trough back-arc rift of the New Hebrides Island Arc (NHIA). The basalts from the SW rift flank of Vate Trough have ages of 0.5 Ma but are geochemically similar to those erupting along the active back-arc rift. The weak subduction component in the back-arc basalts implies formation by decompression melting during early rifting and rifting initiation by tectonic processes rather than by lithosphere weakening by arc magma. Melting beneath Vate Trough is probably caused by chemically heterogeneous and hot mantle that flows in from the North Fiji Basin in the east. The melting zone beneath Vate Trough back-arc is separate from that of the arc front, but a weak slab component suggests fluid transport from the slab. Immobile incompatible element ratios in South NHIA lavas overlap with those of the Vate Trough depleted back-arc basalts, suggesting that enriched mantle components are depleted by back-arc melting during mantle flow. The slab component varies from hydrous melts of subducted sediments in the Central NHIA to fluids from altered basalts in the South NHIA. The volcanism of Erromango shows constant compositions for 5 million years, that is, there is no sign for variable depletion of the mantle or for a change of slab components due to collision of the D'Entrecasteaux Ridge as in lava successions further north.
CRIS-Team Scopus Importer:2020-10-09
Keywords: back-arc basalt; sediment subduction; subduction zone